Implementation of Law Number 8 of 2016 Regarding Legal Protection and Fulfillment of the Rights of Persons with Disabilities in Indonesia - Aliyah, Siti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
sensory limitations who, in interacting with their surrounding environment, still experience obstacles and difficulties in participating fully and actively in society. Apart from having limitations in physical aspects, intellectual limitations, mental limitations, the definition is often also added, namely those who have difficulty participating fully and effectively with other communities. The problem in this research is how is the implementation of Law No. 8 of 2016 regarding the legal protection of persons with disabilities in Indonesia? How is the implementation of Law No. 8 of 2016 towards fulfilling the rights of persons with disabilities in Indonesia? This research method uses a normative juridical approach, with secondary data collection, to prove legal protection and fulfillment of the rights of persons with disabilities. The data obtained was analyzed qualitatively. Based on the research results, it was found that legal protection by the government for people with disabilities is made in the form of statutory regulations such as Law Number 8 of 2016 concerning Persons with Disabilities. However, legal protection is not yet effective and is still repressive in nature. Even though there is a law, discrimination still occurs. This happens because there is little knowledge and awareness among the public, including business actors. The responsibility lies with the government but society itself also causes discrimination against people with disabilities. This law regulates the rights of persons with disabilities to be free from torture or cruel, inhumane, degrading treatment, free from exploitation, violence and ill-treatment, as well as the right to have respect for their mental and physical integrity based on equality with other people. . For this reason, the Government is obliged to realize the rights of persons with disabilities as regulated in this Law, including ensuring the fulfillment of the rights of persons with disabilities in all aspects of life. So that the implementation of respect, protection and fulfillment of the rights of persons with disabilities can be realized optimally.